2007
DOI: 10.1177/0192513x07303881
|View full text |Cite
|
Sign up to set email alerts
|

Childlessness and Parenthood in Two Centuries

Abstract: The article focuses on findings that were replicated across several countries and considers their relevance for future older adults. Key findings are that (a) childlessness makes more of a difference in men's than in women's lives, (b) never-married women are a childless category with particularly favorable characteristics, and (c) childless people face support deficits only toward the end of life. In future cohorts, the authors expect to see (a) clearer contrasts between childless men and fathers, given indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2
35

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 53 publications
5
71
2
35
Order By: Relevance
“…Previous research has consistently shown that permanent childlessness is associated with strong socio-economic positions for women, especially the never married (Dykstra and Hagestad, 2007a). Our findings show an opposite pattern for men; those with children have stronger economic positions than those who have remained childless.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Previous research has consistently shown that permanent childlessness is associated with strong socio-economic positions for women, especially the never married (Dykstra and Hagestad, 2007a). Our findings show an opposite pattern for men; those with children have stronger economic positions than those who have remained childless.…”
Section: Discussioncontrasting
confidence: 66%
“…Fourth, fatherhood shapes men's lives via social control, as the role of father entails certain obligations. By law, parents must not only provide their children with the essentials of daily living such as food and shelter, but also provide socialization for their children's future adult lives (Dykstra and Hagestad, 2007a). There are socially shared expectations about proper behaviour of fathers.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Moreover, after becoming a father, they also more often have children with more than one partner, which indicates that they are more at risk of union separation and divorce. This has implications for the challenges related to an aging population, as childless and single men have been found to be particularly disadvantaged with regard to health and the support potential of their networks (Dykstra and Hagestad 2007). Since children and close family remain a critical source of help for frail old people, (Attias-Donfut, Ogg, and Wolff 2005) this inevitably implies an increased demand for care services and extra pressure on public budgets in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of this development is a stronger increase in childlessness among men than among women in younger Norwegian and Swedish cohorts (Statistics Sweden 2002;Skrede 2004). The challenges may thus be even stronger than judged by the development of the fertility trends for the female cohorts, as childless men have been found to be particularly disadvantaged with regard to health and the support potential of their networks (Dykstra and Hagestad 2007).…”
Section: How Sustainable Is the Nordic Model Of Family Welfare?mentioning
confidence: 99%